Dinamika pada Cerpen Penguntit: Analisis Karakter dalam Cerpen "Penguntit" - Thahira, Putrie Assyfa; Abdurahman, Abdurahman (TSAQOFAH, 2026)
Although mystical elements in short stories have received attention in a number of literary studies, discussion that specifically examines character dynamics in the short story “Penguntit,” particularly in relation to the influence of supernatural elements on changes in characters’ behavior, remains limited in Indonesian literary studies. This study aims to analyze how mystical elements in the short story “Penguntit” influence character development, inner conflict, and social interaction among the characters. This study employed a qualitative approach with a text analysis design, involving three main characters engaged in mystical events. Data were collected through reading and textual analysis of the short story and were then analyzed using thematic analysis to identify themes and character dynamics influenced by supernatural forces. The results show that the characters in the short story undergo significant psychological changes as a result of their interaction with the supernatural world, which subsequently gives rise to social tension among the characters. These findings contribute to the development of character theory in Indonesian literature and broaden understanding of the relationship between character and mystical elements in narrative. This study concludes that characters’ psychological change is an important aspect in the construction of mystical stories, while also underscoring the importance of attention to the impact of supernatural elements in the reading and teaching of Indonesian literary works.